Free-electron Auger quenching of the Fe2+ excited state in ZnSe. (December 2019) - Il'ichev, N.N.; Bufetova, G.A.; Gulyamova, E.S.; Pashinin, P.P.; Sidorin, A.V.; Tumorin, V.V.; Kalinushkin, V.P.; Gavrishchuk, E.M.; Savin, D.V.; Rodin, S.A.; Ikonnikov, V.B.
Abstract: The influence of free electrons in Fe 2+ : ZnSe crystals on the nonlinear transmission of high-power laser radiation with a wavelength of 2940 nm at room and low temperatures is experimentally found. Fe 2+ : ZnSe samples additionally doped with Al are used. The transmission of an Al : Fe : ZnSe sample with electron conduction in a strong (peak intensity about 4.6 MW cm −2 ) field is almost the same as in a weak field both at low and room temperatures. The absence of an increase in the transmission of this sample under the action of high-power radiation is explained by increasing absorption saturation intensity of Fe 2+ at this wavelength due a decrease in the lifetime of the excited state of Fe 2+ . The decrease in the lifetime is related to the well-known Auger quenching of impurity luminescence in semiconductors by free electrons.